Equal protection before the law: a study on the matrimonial rights of women in Afghanistan - Hekmatullah Muradi Faiz Murad (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A)-- Faculty of Shariah and Law, Universiti Sains Islam Malaysia, 2015